2021
DOI: 10.1155/2021/6623912
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology and Molecular Docking-Based Prediction of the Mechanism of Qianghuo Shengshi Decoction against Rheumatoid Arthritis

Abstract: Qianghuo Shengshi decoction (QHSSD) is a classical Chinese medicine formula, which is used in clinical practice for the treatment of rheumatoid arthritis (RA) in China. However, the pharmacological mechanism of QHSSD on RA has remained unclear by now. We collected and screened active compounds and its potential targets by the pharmacology platform of Chinese herbal medicines. In addition, the therapeutic targets of RA were obtained and selected from databases. Network construction analyzed that 128 active comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In the network, each node represented a target gene or molecule, and the connecting line between two nodes represented the relationship between them. It meant the stronger the degree of the node, the greater the role of the target in the network [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the network, each node represented a target gene or molecule, and the connecting line between two nodes represented the relationship between them. It meant the stronger the degree of the node, the greater the role of the target in the network [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The process developed in our study has combined the ADME studies with the multi-level systems biology, instead of blending each herbal medicine's index components in the pharmacopeia. The absorbable components were selected as potential active compounds for further research, which was consistent with serum pharmacology, 64,65 to a certain extent, solving the problem made by the complex components of CHM. In addition, previous studies had shown that the false positive results could be reduced when absorbable components were applied to network pharmacology analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The exploration of natural compounds as possible therapeutic options is widely used, as these compounds are generally expected to have fewer adverse reactions. In silico studies, and molecular docking in particular, have been used to evaluate the potential interaction and potential effects of ginsenosides in targeting the BTK and p38 MAPK signaling pathways, suggesting potential benefits for RA [23,24]. Another in silico study that also used molecular docking showed that compounds from Hedyotis diffusa Willd (i.e., β-sitosterol, quercetin, stigmasterol, kaempferol, 2-methoxy-3-methyl-9,10-anthraquinone) may have a therapeutic effect on RA by modulating the phosphatidylinositol 3-kinase/protein kinase B signaling pathways and targeting TNF-α, IL6, IL-, and target transcription factor p65 [25].…”
Section: Introductionmentioning
confidence: 99%